Gibraltar : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2007)
Gibraltar's Detailed Assessment Report on Anti-Money Laundering (AML) and Combating the Financing of Terrorism is reviewed. The principal AML risk to Gibraltar is lodged in its professional sector, which is likely to be involved in the layering and integration of proceeds of crime. There is also some risk to Gibraltar at the placement stage, in connection with drug trafficking, migrant smuggling, and organized crime in southern Spain. The Financial Services Commission in Gibraltar has established a strong, risk-based framework for financial institutions for AML.